WRONGFUL TRADING: COMPARATIVE APPROACH (ENGLAND AND WALES, RUSSIA AND THE USA) - D. Konstantinov (BRICS Law Journal, 2016)
This paper is designed to discover legal rules addressing insolvency trading in three jurisdictions: England and Wales, Russia and the USA. Originally it was a master’s dissertation written under supervision of Ms. Sarah Paterson, who was extremely helpful and patient. The key jurisdiction for the research is England and Wales, whose wrongful trading provision apparently was the very first insolvency regulation in the field. Here, we will give particular attention to the factual circumstances of insolvency trading and research how the concept of wrongful trading addresses them. The next question will be how the American concept of deepening insolvency and the Russian concept of subsidiary liability are comparable with wrongful trading. Later, we will focus on the functions that should be performed by the regulations. Also, the effectiveness of wrongful trading and similar overseas provisions will be examined. Finally, this paper attempts to find obstacles to the wide application of wrongful trading provision.